Transmit antenna selection for multiple antenna systems with stall avoidance. (February 2017) - Okumu, Elizabeth M.; Dlodlo, Mqhele E.
Highlights: Overall performance of MIMO is improved by cross layer transmit antenna selection. Stalling of packets occurs in the receiver buffer when N-SAW is implemented. Implementing timer based stall avoidance mechanism results in packets being dropped. Larger packets increase latency while reducing the throughput and dropped packets. Increasing the number of SAW processes increases the throughput and dropped packets. Graphical abstract: Abstract: This paper presents an analysis of the performance of transmit antenna selection in multiple-input multiple-output (MIMO) systems with N Stop and Wait (N-SAW) at the data link layer. The impact of packet size, number of SAW processes and the stalling of packets inside the receiver reordering buffer, due to N-SAW, on transmit antenna selection is investigated. Antenna selection is implemented as a signal processing technique that enhances the performance of the MIMO system; two schemes, throughput and capacity based transmit antenna selection are considered. Results show that under similar conditions, throughput maximization outperforms capacity maximization in terms of throughput, transmission latency and dropped packets when stall avoidance is implemented. The results further show that throughput and dropped packets increase with increase in SAW processes and decrease with increase in packet size. Transmission latency increases with increase in packet size and remains unchanged with increase in number of SAW processes.